gamma-Glutamyltransferase-dependent biliary-hepatic recycling of methyl mercury in the guinea pig - Dutczak, W J; Ballatori, N (The Journal of pharmacology and experimental therapeutics, 1992)
After secretion into bile, glutathione (GSH) and GSH-conjugates are catabolized by gamma-glutamyltransferase (gamma-GT) and dipeptidases yielding glutamate, cysteine, glycine and cysteine S-conjugates, and these products are then partially reabsorbed from the biliary tree. Because methyl mercury is thought to be secreted into bile as a GSH- complex, it may be subject to a similar intrahepatic cycle, thus delaying its elimination. To examine this possibility guinea pigs were dosed with 203Hg-methyl mercury (10 mumol/kg i.v.), followed by a retrograde intrabiliary infusion of Krebs-Henseleit buffer (control) or acivicin (an inhibitor of gamma-GT). Acivicin increased biliary excretion of 203Hg by 41%, and GSH from 0.14 +/- 0.10 to 2.02 +/- 0.26 nmol/min.g of liver. Bile analyzed by gel filtration chromatography revealed that CH(3)203Hg-GSH accounted for most of this increased 203Hg excretion. When CH(3)203Hg-complexes of GSH, cysteine and albumin were introduced directly into the biliary tree by retrograde infusion, 203Hg recovery in bile was significantly lower than recovery of the nonabsorbable marker [14C]sucrose, ranging from 26.0 +/- 2.9% for CH(3)203Hg-cysteine to 48.7 +/- 5.1% for CH(3)203Hg-albumin and approximately 60% for [14C]sucrose. Acivicin pretreatment significantly increased 203Hg excretion into bile after retrograde infusion of CH(3)203Hg-GSH, whereas 203Hg recovery after retrograde infusion of CH(3)203Hg-cysteine remained constant.